Analisis Bibliometrik Publikasi Ilmiah Tentang Sistem Informasi Perpustakaan dengan Pendekatan Co-occurrence - Dewa Sasikirana, Priaji; Kamil Muhtadin, Hisyam (Jurnal Tadwin, 2024)
Library information system is a computerized process to process data in a library. Everything is processed using certain software such as database processing software. Library staff can always monitor the availability of books, new book lists, book loans, and book returns. So compared to conventional libraries, library information systems make it easier for library staff and library users to manage and borrow books. This study uses a quantitative descriptive method based on bibliometric investigations. The scope of data used is scientific publication articles about library information systems based on searches using the Google Scholar database. The publication articles come from national journals with the limitation that the publication articles used in this research are published in open access or can be accessed in terms of author, publisher, year of publication, author keywords. Shows the co-occurrence map with library information system keywords taken from 2019-2024 formed into 46 clusters, indicating the diversity of sub-topics or aspects in library information system research. Here it can be seen that "library" and "information system" have the largest shape which indicates the most used keywords. Through co-occurrence analysis there was a significant increase in the number of publications on library information systems, especially in 2022 and 2023, indicating that this topic is increasingly relevant and of interest to researchers. The keyword connection map on VOSviewer shows that "library" and "information system" are the most frequently occurring keywords, illustrating the close relationship between these concepts in research.